Foreign direct investment, economic freedom and economic performance in Sub-Saharan Africa - Ajide, Kazeem Bello (Managing global transitions, 2015)
The controversies that trailed whether direct impact of Foreign Direct Investment (FDI) on growth are conditional on a certain intermediating links or not, has made an inquiry into the likely mediating links in the FDI growth space a recurring subject of discourse. While the importance of institution has prominently featured as playing a vital role on the one hand, economic freedom (a key institutional component) has consistently been elected, as a good candidate surrogate on the other hand. It is against this backdrop this study examines the effect of FDI inflow on economic performance in the ssa region giving prominence to economic freedom. The results support the view that economic freedom is germane in influencing the economic-wide performance in the region but have insignificant effects on the different sector performances. It is recommended that economic freedom be given priority in the region and fdi should be attracted to other sectors other than the primary sector, as it is the case.
Keywords: economic freedom; podsaharska Afrika; economic performance; ekonomski razvoj; neposredne tuje investicije; panel data analysis; gospodarska svoboda; FDI priliv; gospodarska storilnost; analiza panelne ankete; FDI inflow